The Integration Of Technology: The Role Of Technological Pedagogical Content Knowledge and Self-Efficacy - Aprilyani, Nina; Mentari, Sriyani (Universitas Negeri Malang, 2023)
Technology-mediated learning equips students with the skills to compete in the 21st century. Therefore, teachers as holders of an important role must have the ability to facilitate and create this learning environment. Higher education institutions have a role in providing various knowledge and abilities to students as prospective teachers to feel ready and able to integrate technology into learning effectively. This research aims to explore students' internal factors, especially TPACK and self-efficacy, which influence the integration of technology into learning. The research method uses an explanatory quantitative approach. The research sample was 132 accounting education students at the State University of Malang who took part in teaching assistance activities using proportional stratified random sampling. Data collection is distributed via G-Form and analyzed using multiple regression analysis. The results of the research show that technological pedagogical content knowledge and student self-efficacy have a positive and significant effect on the integration of technology into learning so that better TPACK and self-efficacy in students will make students more often integrate technology into learning in the future classroom. Therefore, this research is expected to provide material and insight for students regarding internal factors (TPACK and self-efficacy) related to the integration of technology into learning.